The doppel (Dpl) Protein Influences In Vitro Migration Capability in Astrocytoma-Derived Cells - Alberto Azzalin; Elena Sbalchiero; Giulia Barbieri; Silvia Palumbo; Cristina Muzzini; Sergio Comincini (Cellular Oncology)
Doppel (Dpl) protein is the paralogue of the cellular prion (PrPC) protein. In humans, Dpl is expressed almost exclusively in testis where it is involved in spermatogenesis. Recently, the protein has been described to be ectopically expressed in astrocytomas and its potential association to the brain tumor malignancy progression has been advanced. In this study, we aimed to investigate in vitro the potential involvement of Dpl in the tumor cell migration: to this purpose, Dpl expression was reduced in the IPDDC-A2 astrocytoma-derived cell line, by means of antisense and siRNA approaches; migration rates were then evaluated by means of a scratch wound healing assay. As a result, the cellular migration was sensibly reduced after Dpl silencing. Following a complementary approach, in HeLa cells, showing very low endogenous Dpl expression, the protein expression was induced by transfection and stabilization of an eukaryotic expression vector containing the doppel gene coding sequence. These stably Dpl-overexpressing cells revealed a significant increase in the migration rate, compared to untreated and control cells. In addition, Dpl-forced expression induced substantial changes in the cell morphology. Of note, in these cells, viability examination by means of tetrazolium-based assay did not reveal differences in the proliferation; on the contrary, a variation in density-dependent growth, leading to an increase of cell contact inhibition was highlighted. These results, in conclusion, might suggest a potential and functional role for Dpl in tumor cells migratory and morphological behaviours and address to future gene-targeted therapeutic interventions.